PHYTOCHEMICAL AND ANTIOXIDANT ACTIVITY OF BALIOSPERMUM MONTANUM (WILLD.) MUELL. ARG. - RAVEESHA HR; SUSHMA BK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was carried out to evaluate the phytochemical constituents and antioxidant potential of the leaf, stem, root, and stem-derived callus extracts of Baliospermum montanum. Methods: An in vitro regeneration protocol was developed for the induction of callus from stem segments cultured on Murashige and Skoog (MS) medium supplemented with different concentrations and combination of 6-benzylaminopurine (BAP), 6-furfurylaminopurine (KIN), 1-naphthaleneacetic acid, and 2, 4-dichlorophenoxyacetic acid. The total phenol, flavonoid, and tannin content were determined according to standard methods. The antioxidant activity of methanolic extract was evaluated using 2, 2-diphenyl-l-picrylhydrazyl (DPPH) and reducing power assays. Results: The maximum callus induction was observed on MS medium supplemented with a combination of KIN (0.5 mg/L) + BAP (3.0 mg/L). Methanolic extract of root and aqueous extract of leaf exhibited higher content of phenols. Whereas total flavonoids and tannin were maximum in methanolic extract of leaf compared to other extracts. The methanolic extract of B. montanum leaf had greater antioxidant activity than stem, root, and callus by DPPH and reducing power assays. Conclusion: Our study suggests that the methanolic extracts of B. montanum showed potent free radical scavenging activity. Further studies are necessary for isolation and characterization of phytochemical compounds.